P.215 Tumor Heatmaps – Feedback Tool for Virtual Reality Neurosurgical Simulation. (November 2021) - Sawaya, R; Yilmaz, R; Bugdadi, A; Winkler-Schwartz, A; Azarnoush, H; Alsideiri, G; Del Maestro, R
Abstract : Background: Performance Heatmaps were designed to visualize the spatial distribution of performance metrics during resection of complex tumors. This novel methodology provides experts (neurosurgeons) and trainees (residents and medical students) with visual feedback on their neurosurgical performance during operative procedures. Methods: Neurosurgeons (NS), senior residents (SR), junior residents (JR) and medical students (MS) performed resection of a complex tumor on the NeuroVR simulation platform. Metrics including time spent, force applied, and tumor volume removed were used to create Performance Heatmaps for each group. Results: During complex operative procedures, greater expertise correlated increased time spent in critical areas (NS = 121.0 s, SR = 103.0 s, JR = 86.1 s, MS = 84.9 s), increased force application (NS = 387 N, SR = 317 N, JR = 340 N, MS = 304 N), and increased tumor removal (NS = .096 cc, SR = .081 cc, JR = .074 cc, MS = .069 cc). Conclusions: Performance Heatmaps further our understanding of neurosurgical expertise by identifying key differences between experts (neurosurgeons) and trainees (residents and medical students). With the adoption of competency-based curricula, intuitive feedback tools will prove essential for trainees seeking surgical mastery.